PENGARUH PEMBERIAN AIR LIMBAH TEMPE TERHADAP PERTUMBUHAN AYAM KAMPUNG - Shaleh Abdullah; Soegeng Herijanto; Supranoto (MEDIA PETERNAKAN, 2023)
The research "The Effect of Providing Tempe Wastewater on the Growth of Kampung Chicken” aims to determine the growth of kampung chickens that were given tempe waste water and to find out the difference in growth weight of chickens. The material used was 4 weeks old free-range chicks totaling 40. The method used was a completely randomized design (CRD) with 4 treatments and 5 replications so that there were 20 experimental units. Each experimental unit was filled with 2 chickens. The treatment of tempe wastewater consisted of P0 (120 ml water in 80 grams of feed), P1 (40 ml of temped wastewater and 80 ml of plain water), P2 (80 ml of tempe wastewater and 40 ml of plain water), P3 ( 120 ml of tempe wastewater). The variables observed were body weight gain, feed consumption, Feed Conversion Ratio (FCR). Analysis of variance showed that the provision of tempe wastewater had no effect (P>0.05) on daily body weight gain, daily feed consumption and Feed Conversion Ratio kampung chicken. Keywords : kampung chicken, tempe wastewater, daily body weight change, daily feed consumption, feed conversion ratio (FCR).